2021
DOI: 10.3390/atmos12081017
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Annual Variation of Stem Circumference of Tree Species Prevailing in Hemi-Boreal Forest on Hourly Scale in Relation to Meteorology, Solar Radiation and Surface Ozone Fluxes

Abstract: (1) Background: Continuous monitoring of the tree stem increment throughout the year is crucial for the understanding of trees’ reactions to changes in meteorology, solar radiation and surface ozone and evaluating the adaptive capacity of prevailing tree species to recent environmental global changes; (2) Methods: Data on tree intra-annual sequences based on electronic dendrometer data of Picea abies (L.) Karst, Pinus sylvestris L., Betula pendula, and Betula pubescens, growing under different nutritional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Its drought sensitivity depends on site related factors especially on relief, topography and soil characteristics such as rooting and water holding capacity of soils (Levesque et al, 2014). Therefore, the reactions of this considered tree species to extreme meteorological events under different growth conditions differed significantly due to their different strategies (McDowell 2008;Augustaitis et al, 2018;Marozas et al, 2019) when surviving first of all heat and drought episodes (Lévesque et al, 2014;Augustaitis 2021) what quite well indicates their needles spectral reflectance (Masaitis et al, 2013(Masaitis et al, , 2014. This finding well agreed with results obtained on annual scale which indicated that meteorology explained variation in annual pine tree ring width variation more significantly than acidifying compounds (Augustaitis et al, 2007b(Augustaitis et al, , 2015(Augustaitis et al, , 2018Juknys et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Its drought sensitivity depends on site related factors especially on relief, topography and soil characteristics such as rooting and water holding capacity of soils (Levesque et al, 2014). Therefore, the reactions of this considered tree species to extreme meteorological events under different growth conditions differed significantly due to their different strategies (McDowell 2008;Augustaitis et al, 2018;Marozas et al, 2019) when surviving first of all heat and drought episodes (Lévesque et al, 2014;Augustaitis 2021) what quite well indicates their needles spectral reflectance (Masaitis et al, 2013(Masaitis et al, , 2014. This finding well agreed with results obtained on annual scale which indicated that meteorology explained variation in annual pine tree ring width variation more significantly than acidifying compounds (Augustaitis et al, 2007b(Augustaitis et al, , 2015(Augustaitis et al, , 2018Juknys et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Such changes could affect also trees resistance to pest damage (Augustaitis, 2007). Long-term analysis of meteorological data for a gradient from the coastal to eastern inner Lithuania revealed an increase in annual air temperature and precipitation and rising variation in monthly patterns during the period 1981-2020 compared to 1950-1980 (Augustaitis et al, 2018(Augustaitis et al, , 2021. The lack of atmospheric humidity is predicted to reinforce negative effect of climate warming in southern and central parts of Europe, meanwhile in northeastern part of Europe, including Lithuania gradual increase in precipitation amount should mitigate this negative effect of climate changes increasing tree increment (Augustaitis et al, 2015(Augustaitis et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation